2004
DOI: 10.1211/0022357044715
|View full text |Cite
|
Sign up to set email alerts
|

Role of the carboxylic group in the antispasmodic and vasorelaxant action displayed by kaurenoic acid

Abstract: The present work describes the investigation of the role of the carboxylic group in the structure-activity relationship of the diterpene ent-kaur-16-en-19-oic acid (kaurenoic acid, KA) in inhibiting rat aorta contraction. For this purpose the methylation of the C-19 carboxyl group of KA was carried out. The effects of the obtained ent-methyl-kaur-16-en-19-oate (KAMe) were compared with those induced by KA. Vascular reactivity experiments showed that KA (50 and 100 microM) concentration-dependently inhibited KC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
7
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 8 publications
5
7
0
Order By: Relevance
“…These insaturations produce a conformational restriction and seem to account for the activity showed by these fractions. The carboxylic group present in these compounds seems to play an important role in inhibiting rat aorta contraction which is in agreement with the results shown by several kaurane (Ambrosio et al, 2004) and labdane-type diterpenoids (Lahlou et al, 2006).…”
Section: Resultssupporting
confidence: 90%
“…These insaturations produce a conformational restriction and seem to account for the activity showed by these fractions. The carboxylic group present in these compounds seems to play an important role in inhibiting rat aorta contraction which is in agreement with the results shown by several kaurane (Ambrosio et al, 2004) and labdane-type diterpenoids (Lahlou et al, 2006).…”
Section: Resultssupporting
confidence: 90%
“…About 30 g of a crude dichloromethane extract of the roots of Viguiera arenaria, which was previously prepared in our laboratory, was suspended in a solution of CH3OH/H2O (9:1, v/v) and partitioned with n-hexane and dichloromethane according to Ambrosio et al [3]. The n-hexane fraction (6.75 g) was re-fractioned using vacuum liquid chromatography [12] and yielded seven new fractions (Fr1-Fr7).…”
Section: Isolation Of Pimaradienoic Acidmentioning
confidence: 99%
“…Increased attention has been paid in recent years to the study of the biological effects of diterpenes, a recognized class of natural compounds with a broad spectrum of biological activities such as antiparasitic [1], anti-inflammatory [2], and antispasmodic properties [3]. Among these metabolites, the pimarane-type diterpene, ent-pimara-8 (14),15-dien-19-oic acid (pimaradienoic acid, PA; Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, a chemical blockade of the carboxylic group at the C-19 of kaurenoic acid was carried out and the effects of the methyl ester derivative obtained were compared with those induced by kaurenoic acid [44]. Vascular reactivity experiments, using standard muscle bath procedures, showed that kaurenoic acid was more effective at inhibiting CaCl 2 and KCl-induced contraction than its methyl ester derivative.…”
Section: Inhibitory Action Of Kaurane-type Diterpenes On Extracellulamentioning
confidence: 99%